The association and clinicopathological significance of Integrin alphavbeta6 and Rac1 expression in gastric carcinoma - Junjian Yu; Wenyu Jia; Qi Liu; Antai Yuan; Zhuoyu Jia; YuQi Sun; Zequn Li; Shougen Cao (Frontiers in Oncology, 2024)
BackgroundThe present study investigate the expression and correlation of ITGB6 and Rac1 proteins in gastric cancer tissues. By exploring the clinical significance and functions of these proteins, we aimed to gain further insights into the mechanisms underlying gastric cancer development.Patients and methodsIn this study, a total of 198 patients diagnosed with gastric cancer and who underwent gastrectomy between July 2010 to October 2012 were included. The median follow-up time was 52.00 months. To evaluate the factors influencing overall survival, Kaplan-Meier survival curve analysis and Cox regression analysis were conducted. Furthermore, an independent prognostic factor-based nomogram was constructed and validated to predict survival outcomes in gastric cancer patients. In addition, in vitro experiments including CCK8 and Transwell assays were conducted to explore the roles of ITGB6 and Rac1 in gastric cancer.ResultsThe expression levels of ITGB6 and Rac1 in gastric cancerous and paraneoplastic tissues were detected by immunohistochemistry. The correlation and clinical significance of the two proteins were also investigated. ITGB6 expression showed significant associations with tumor size (P=0.030), pathological grading (P=0.013), location (P=0.031), N stage (P=0.002), and clinical stage (P=0.002). Additionally, we found that tumor size (P=0.013), tumor’s anatomical location (P=0.031), N stage (P=0.002), clinical stage (P=0.035), and survival status (P<0.001) were significantly associated with the expression of Rac1. ITGB6 was moderately correlated with Rac1 (r=0.285, P<0.001). Both the Kaplan-Meier survival analysis and Cox regression model analysis demonstrated that the presence of positive expression of ITGB6 and Rac1 proteins served as independent prognostic factors for gastric cancer. These findings highlight the potential of ITGB6 and Rac1 as valuable markers for predicting the prognosis of gastric cancer patients (HR=2.212 P<0.001 and HR=2.073 P=0.001), with a significant poorer trend for 5-year survival (P<0.0001, respectively, the log-rank test). Additionally, subsequent in vitro experiments preliminarily demonstrated that ITGB6 and Rac1 promoted the proliferation, migration and invasion of gastric cancer cells, and ITGB6 may functions via targeting Rac1.ConclusionITGB6 and Rac1 are indicators of poor prognosis and tumor progression in gastric cancer patients. The potential signaling pathways associated with both may provide useful targets for the prevention and treatment of gastric cancer.